2017
DOI: 10.1152/ajpgi.00197.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NK1 receptors on gastric motor functions and satiation in healthy humans: results from a controlled trial with the NK1 antagonist aprepitant

Abstract: Aprepitant, an NK1 receptor antagonist, is approved for the treatment of chemotherapy-induced or postoperative emesis by blocking NK1 receptors in the brain stem vomiting center. The effects of NK1 receptors on gastric functions and postprandial symptoms in humans are unclear; a single, crossover study did not show a significant effect of aprepitant on gastrointestinal transit. Our aim was to compare, in a randomized, double-blind, placebo-controlled, parallel-group study (12 healthy volunteers per group), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 25 publications
0
28
1
4
Order By: Relevance
“…The finding that cotreatment with the NK1/substance P receptor antagonist aprepitant abolished the increase in norepinephrine suggests that substance P mediates stimulation of the sympathetic nervous system. Importantly, aprepitant does not significantly affect gastric transit time [35]. The finding that norepinephrine was increased by sitagliptin during valsartan as well as during ramipril, however, indicates that the mechanism involves a pharmacodynamic interaction between substance P and the RAAS rather than a pharmacokinetic effect of ACE inhibition and DPP4 inhibition on substance P. Unfortunately, we were not able to measure endogenous substance P using a specific assay in this study.…”
Section: Discussionmentioning
confidence: 90%
“…The finding that cotreatment with the NK1/substance P receptor antagonist aprepitant abolished the increase in norepinephrine suggests that substance P mediates stimulation of the sympathetic nervous system. Importantly, aprepitant does not significantly affect gastric transit time [35]. The finding that norepinephrine was increased by sitagliptin during valsartan as well as during ramipril, however, indicates that the mechanism involves a pharmacodynamic interaction between substance P and the RAAS rather than a pharmacokinetic effect of ACE inhibition and DPP4 inhibition on substance P. Unfortunately, we were not able to measure endogenous substance P using a specific assay in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Also, neurokinin antagonists are approved for the treatment of chemotherapy-induced emesis 126. Among these drugs, aprepitant, increases gastric accommodation127 and improves some digestive symptoms in patients with gastroparesis,128 but does not affect GE 127. Although the APRON Trial failed to show positive results on the primary end point of nausea, several other secondary end points showed improvement with aprepitant 128.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in mice showed that maropitant administration reduced intestinal motility and delayed intestinal transit time of labeled luminal contents (Mikawa et al, ). Similarly, humans using similar NK‐1 receptor antagonists have reported side effects of constipation in up to 16% of patients studied in one population (Jacob et al, ; Li et al, ). Peer‐reviewed data are unavailable describing intestinal motility disorders associated with maropitant in species other than mice, and further investigation is warranted prior to administering maropitant to horses at risk for gastrointestinal impaction.…”
Section: Discussionmentioning
confidence: 90%